2020
DOI: 10.1111/fog.12499
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation in the coastal distribution of a juvenile gadid in the northeast Pacific Ocean: The relevance of wind and effect on recruitment

Abstract: Drift of propagules occurs within many populations inhabiting flow fields. This affects the number of propagules that rejoin their source population (recruitment) and plays a role in adaptive spatial redistribution. We focus on the cause and consequence of interannual variation in geographic distribution of population density among five cohorts of young-of-the-year (age-0) juvenile walleye pollock Gadus chalcogrammus in the western Gulf of Alaska (GOA). The coastal GOA is a wind-driven advective system. Walley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Modeled May–June transport speed though Shelikof based on the Hybrid Coordinate Ocean Model (HYCOM) indicated slow current speeds in 2015 relative to other years 1991–2017 (Kimmel & Duffy‐Anderson, 2020), again suggesting retention as opposed to advection. Retention of larvae is consistent with observed surface winds, which lacked a strong southward component, and the buildup of low salinity water in 2015 (Wilson & Laman, 2020). Timing and location of spawning may affect the ultimate drift trajectory of eggs and larvae (Hinckley et al., 2001), but neither was anomalous in 2015 (McCarthy et al., 2016; Rogers & Dougherty, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…Modeled May–June transport speed though Shelikof based on the Hybrid Coordinate Ocean Model (HYCOM) indicated slow current speeds in 2015 relative to other years 1991–2017 (Kimmel & Duffy‐Anderson, 2020), again suggesting retention as opposed to advection. Retention of larvae is consistent with observed surface winds, which lacked a strong southward component, and the buildup of low salinity water in 2015 (Wilson & Laman, 2020). Timing and location of spawning may affect the ultimate drift trajectory of eggs and larvae (Hinckley et al., 2001), but neither was anomalous in 2015 (McCarthy et al., 2016; Rogers & Dougherty, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…The percent variance in age‐2 recruitment explained by age‐0 abundance was highest in the Kodiak (96%) and Shelikof (88%) regions, our domains C and B, respectively. Lastly, Wilson and Laman (2020) found no significant relationships between age‐0 abundance and age‐2 recruitment for the southwest region, our Domain A.…”
Section: Discussionmentioning
confidence: 57%
“…In summary, we believe that poor recruitment of the 2013 age‐0 pollock year class in the WGOA was mostly likely due to the combined effects of sub‐optimal diet in a large portion of the population (this study), wind‐driven advection of a large proportion of the population to the southwest (Wilson & Laman, 2020), and perhaps cannibalism from the 2012 year class. A large portion of age‐0 pollock consumed less energy‐rich prey could decrease the chances of reaching an adequate weight necessary for overwinter survival.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…When testing this hypothesis, Dannevig (1907) found a positive correlation between estuarine commercial catch rates and onshore winds lagged by three or four years (Suthers et al, 2020). Since the inception of this hypothesis, many studies have shown relationships between wind and juvenile recruitment with the effects largely being system specific (Nelson et al, 1977;Caputi et al, 2001;Takeshige et al, 2013;Wilson and Laman, 2021), likely due to complex estuary specific recruitment processes (Boehlert and Mundy, 1988).…”
Section: Introductionmentioning
confidence: 99%